Analysis of the evolution of sustainable development in biofuels industry in Brazil - Rollano, Carmen Rosa Loayza (2015)
This paper presents an evaluation of sustainable development in the biofuel production sector. The Energy Indicators Tool for Sustainable Development (EISD) and the Sustainability Indicators Tool Global Association for Bioenergy (GBEP) were applied. Performing a comparison of indicators in each performance (economic, social and environmental), it was found that the production of biofuels in Brazil is positive in most of them. Biofuels showed a favorable trend in economic indicators, not only in terms of cost, but also through the use of energy available to the consumer market. Environmental indicators showed an improvement in the efficient use of land, water and energy resources, while pesticide applications are relatively low in relation to the limits. In addition, it appears that the biofuels industries have contributed positively to rural economies, since the social indicators showed a relatively significant and positive increase in labor supply and salary level of the labor market in this sector. Also appears that existing tools are complementary and the results provide a basis for future discussions and the development of sustainability assessments in systems and bioenergy-related projects.